Transcriptional Regulation of Liver-Type OATP1B3 (Lt-OATP1B3) and Cancer-Type OATP1B3 (Ct-OATP1B3) Studied in Hepatocyte-Derived and Colon Cancer-Derived Cell Lines - Haberkorn, Bastian; Löwen, Dennis; Meier, Lukas; Fromm, Martin; König, Jörg (Pharmaceutics, 2023)
Due to alternative splicing, the SLCO1B3 gene encodes two protein variants; the hepatic uptake transporter liver-type OATP1B3 (Lt-OATP1B3) and the cancer-type OATP1B3 (Ct-OATP1B3) expressed in several cancerous tissues. There is limited information about the cell type-specific transcriptional regulation of both variants and about transcription factors regulating this differential expression. Therefore, we cloned DNA fragments from the promoter regions of the Lt-SLCO1B3 and the Ct-SLCO1B3 gene and investigated their luciferase activity in hepatocellular and colorectal cancer cell lines. Both promoters showed differences in their luciferase activity depending on the used cell lines. We identified the first 100 bp upstream of the transcriptional start site as the core promoter region of the Ct-SLCO1B3 gene. In silico predicted binding sites for the transcription factors ZKSCAN3, SOX9 and HNF1α localized within these fragments were further analyzed. The mutagenesis of the ZKSCAN3 binding site reduced the luciferase activity of the Ct-SLCO1B3 reporter gene construct in the colorectal cancer cell lines DLD1 and T84 to 29.9% and 14.3%, respectively. In contrast, using the liver-derived Hep3B cells, 71.6% residual activity could be measured. This indicates that the transcription factors ZKSCAN3 and SOX9 are important for the cell type-specific transcriptional regulation of the Ct-SLCO1B3 gene.
CRIS-Team Scopus Importer:2023-04-14
Keywords: colorectal carcinoma; Ct-OATP1B3; Ct-SLCO1B3; HNF1α; Lt-OATP1B3; Lt-SLCO1B3; SOX9; ZKSCAN3